On violence : a philosophical dialogue - Pappas, Nicholas J. (Algora Publishing, 2022)
"Violence and reason are related, if only because violence is done to reason every single day. All it takes is to fail to listen. Everything else, all the real violence, starts right there, including tough talk in lieu of rational argument and the violence of not allowing us to think things through. In a virtual conversation with other thoughtful people, we can evaluate and refine our own positions, gaining clarity and confidence"--